(untitled) - Bronze, Michael S. (Norfolk, 2005)
"...This book is an encyclopedic source of valid data that should not be lacking from the book collections of hospitals, general practitioners, and all others with a professional (or national defense) interest in infectious diseases and their complications."
Keywords: Bioterrorism,Communicable diseases; Prevention,Research,Research